Elaboration of a mix design for the stabilization of soil with asphalt emulsion type CSS-1h and recycled asphalt pavement (RAP) based on the modified Marshall procedure - Maylle Paima, Alexandra (2023)
The objective of this research was to develop a cold mix design for the stabilization of a recycled soil with slow breaking cationic asphalt emultion with low viscosity and higher degree of hardness (CSS-1h), based on the Modified Marshall design method. The work consisted in extracting soil samples from a deteriorated pavement for the elaboration of briquettes with emultion percentages between 3% and 6% varying in intervals of 0.5%, then these were tested for the calculation of the volumetric and mechanical properties, to finally determine the optimal percentage of emultion. The maximum resistance (stability) of the mixture was obtained with a dosage of 4.8% asphalt emultion and 2.88% asphalt residue, achieving a maximum value of 980 kg. In conclusion, the stabilization of the material with the proposed dosage led to good results, complying with the minimum stability of 227 kg (500 lb) required by the specifications of the Highway Manual EG-2013.